Immediate Effect of Dry Needling at Myofascial Trigger Point on Hand Spasticity in Chronic Post-stroke Patients: A Multicenter Randomized Controlled Trial - Zhang, Zengqiao; Wang, Wu; Song, Yongjia; Zhai, Tianjun; Zhu, Yan; Jiang, Liming; Li, Qunfeng; Jin, Lei; Li, Kunpeng; Feng, Wei (Frontiers in Neurology, 2021)
Background: Hand spasticity after stroke influences the rehabilitation of hand function. Immediate and effective relief of spasticity potentially creates conditions for later rehabilitation training, which has far-reaching significance in the smooth transition of patients to the recovery period. Objective: To evaluate the immediate effect of dry needling (DN) at myofascial trigger point on hand spasticity in stroke patients. Methods: This was a prospective, evaluator blind, multicenter, randomized controlled study. A total of 210 participants were randomly divided into DN group (DN, N = 70), sham dry needling group (SDN, N = 70), and control group (N = 70). Participants in the DN group were treated with DN at myofascial trigger point five times (30 min each time) every week for 4 weeks. Subjects in the SDN group were manipulated the same way as in the DN group, except that the acupuncture site was located in the area adjacent to the myofascial trigger point, which constituted a SDN. Routine rehabilitation treatment was performed for participants in the two groups and in the control group. The primary evaluation index was the immediate effect of hand spasticity relief. Secondary evaluation indicators included the cumulative effect of hand spasticity relief from baseline to week 4, and the changes in flexion angles of the wrist, thumb, and fingers 2–5 in the rest position before, immediately after, and 4 weeks after intervention. Results: The immediate effective rate of spasticity relief (thumb, fingers 2–5, and wrist) of patients with different degrees of spasticity in the DN group was higher than that in the control and SDN groups (thumb, χ2 = 55.833, P < 0.001; fingers 2–5, χ2 = 68.096, P < 0.001; wrist, χ2 = 49.180, P < 0.001) (P < 0.05). The effective rate of spasticity relief from baseline to 4 weeks in the DN group exceeded that in the control group and SDN groups (thumb, χ2 = 8.806, P = 0.012; fingers 2–5, χ2 = 8.087, P = 0.018; and wrist, χ2 = 8.653, P = 0.013) (P < 0.05). No difference in immediate and cumulative effect was found between the control group and SDN group. The change of joints flexion angles in resting position before and after each treatment in the DN group was higher than that in the control and SDN groups (P < 0.05), but it was not significantly different between the control group and SDN group. At 4 weeks, although the change in the DN group was higher than that in the control group and SDN group, this difference was not statistically significant (P > 0.05). Conclusion: Dry needling can relieve varying degrees of hand spasticity instantly in post-stroke. Trial Registration:www.chictr.org.cn, ChiCTR1900022379.